PENGARUH PEMANFAATAN MEDIA E-LEARNING DAN KEMANDIRIAN BELAJAR TERHADAP KREATIVITAS MAHASISWA PADA MATA KULIAH ANALISA LAPORAN KEUANGAN FKIP EKONOMI ANGKATAN 2017 UNIVERSITAS HKBP NOMMENSEN TAHUN AJARAN 2020/2021 - Juliver nainggolan (Jurnal Ilmu Sosial Dan Politik, 2021)
This study aims to determine the effect of the use of e-learning media and independent learning on student creativity in the Economics Faculty of Economics Financial Report analysis course, class of 20017, University of HKBP Nommensen, Academic Year 2020/2021. This research was conducted at the University of HKBP Nommensen Medan FKIP Economics. The results of this study indicate that the use of e-learning in learning is very helpful for students / students to increase learning activities, honesty and having an independent personality. The phenomenon that occurs also illustrates that during the COVID-19 pandemic, students increase their learning independence. The use of e-learning media and independent learning has a positive effect on student creativity in the financial report analysis course for the economic education study program for the 2020/2021 academic year with the equation Y= 10.061 + 0.433X1 + 0.461X2.